Beam Maps of the Canadian Hydrogen Intensity Mapping Experiment (CHIME) Measured With a Drone - Will Tyndall; Alex Reda; J. Richard Shaw; Kevin Bandura; Arnab Chakraborty; Mark Halpern; Maile Harris; Emily Kuhn; Joshua Maceachern; Juan Mena-Parra; Laura B. Newburgh; Anna Ordog; et al. (IEEE Open Journal of Antennas and Propagation)
We present beam measurements of the CHIME telescope using a radio calibration source deployed on a drone payload. During test flights, the pulsing calibration source and the telescope were synchronized to GPS time, enabling in-situ background subtraction for the full $N^{2}$ visibility matrix for one CHIME cylindrical reflector. We use the autocorrelation products to estimate the primary beam width and centroid location, and compare these quantities to solar transit measurements and holographic measurements where they overlap on the sky. We find that the drone, solar, and holography data have similar beam parameter evolution across frequency and both spatial coordinates. This paper presents the first drone-based beam measurement of a large cylindrical radio interferometer. Furthermore, the unique analysis and instrumentation described in this paper lays the foundation for near-field measurements of experiments like CHIME.